The dual role of p63 in cancer - Xu, Yongfeng; Yang, Xiaojuan; Xiong, Qunli; Han, Junhong; Zhu, Qing (Frontiers in Oncology, 2023)
The transcription factors of the p53 family comprise three proteins: p53, p63, and p73. As extensively described, the p53 family, a widely known cell regulator, adjusts a series of phenotypic and genomic alterations related to crucial cancer progression such as cell proliferation, division, genomic stability, cell cycle arrest, senescence, and apoptosis. In response to extra or intracellular stress or oncogenic stimulation, all members of the p53 family are mutated structure or alerted in expression levels to affect the signaling network, coordinating, among many other pivotal cellular processes. The existence of p63 exists as two main isoforms (TAp63 and ΔNp63) have been discovered, oppositely, TA and ΔN isoforms exhibit distinguished properties by promoting or inhibiting cancer progression. As such, p63 isoforms compose a full mysterious, and challenging regulatory pathway. New insights have recently been gained into the complexity of the p63 regulation of the DNA damage response (DDR) and how it impacts a wide variety of cellular processes. In this review, we will highlight the significance of how p63 isoforms in response to DNA damage and cancer stem cells, as well the dual role of TAp63 and ΔNp63 in cancer.